Staphylococcal Plasmids, Transposable and Integrative Elements - Firth, N.; Jensen, S.; Kwong, S.; Skurray, R.; Ramsay, Joshua (American Society for Microbiology, 2018)
Strains of Staphylococcus aureus, and to a lesser extent other staphylococcal species, are a significant cause of morbidity and mortality. An important factor in the notoriety of these organisms stems from their frequent resistance to many antimicrobial agents used for chemotherapy. This review catalogues the variety of mobile genetic elements that have been identified in staphylococci, with a primary focus on those associated with the recruitment and spread of antimicrobial resistance genes. These include plasmids, transposable elements such as insertion sequences and transposons, and integrative elements including ICE and SCC elements. In concert, these diverse entities facilitate the intra- and inter-cellular gene mobility that enables horizontal genetic exchange, and have also been found to play additional roles in modulating gene expression and genome rearrangement.